KONSISTENSI SIKAP OJEK KONVENSIONAL TERHADAP KEMUNCULAN GOJEK DI KOTA DENPASAR - Alfiani, Unila Ulfa; Suka Arjawa, I Gst Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRAK The appearance Gojek with concept of transformation for ojek conventional by combining technology and ojek services trigger the pros and cons in there society. This research would to explain types of rejection from ojek conventional for appearance Gojek in Denpasar City and influence aspects toward consistency from ojek conventional. This research was qualitative methods using the rational choice theory’s James S. Coleman and the social action theory’s Max Weber. The results of this study about rejection from ojek conventional for appearance Gojek it doesn’t physical conflict directly. Their consistency set of social ties, solidarity, a system or a different way of working. Resources owned by actor or an ojek conventional: ojek member on base, users of ojek conventional, the base is still affordable for all people. There are 4 types of ojek conventional action: the act of instrumental rationality be based on economic needs, the act of value rationality on ojek conventional has structure it also reflects, the act of affection rationality (affectual action) related users of ojek conventional or passengers were satisfied with the service made an ojek conventional have customer remain and the act of traditional rationality such as the system bargaining or negotiation of price with passengers, as well it was usage a long time ago. Keywords: Ojek conventional, Gojek Consistency, Rejection